OHIDAS Toolkit, the PHC, and Tanya Pakar: A Multi-level, Vertically Integrated Digital Health Promotion, Primary Prevention and Telemedicine Provision Programme - Nicholas Pang Tze Ping; Helen Benedict Lasimbang; Mohd. Hanafi Ahmad Hijazi; Mohd Nizar Bin Hamild; Mohd Azhar Bin Dris; Wendy Shoesmith; Fumihiko Yokota; Rafiqul Islam Maruf; Naoki Nakashima (Japan Association for Medical Informatics, 2020)
Multiple challenges abound in Malaysian healthcare delivery, including a high prevalence of non-communicable disease associated with poorly reinforced lifestyle practices, service delivery challenges in primary care, and difficulty in adapting English-language evidence-based research to Kadazan culturespecific health beliefs. University Malaysia Sabah (UMS) University Hospital (HUMS) conceptualized a three-pronged, vertically integrated digital health system to address these shortfalls intelligently. Firstly, a mobile application called OHIDAS (“health” or “wellness” in the local Kadazan language) was built to serve two major objectives namely promoting healthy lifestyle practices among the community and advocating for health screening prior to illness to maintain health and well-being in our communities and prevent illness caused through NCDs. There are four stages of OHIDAS; health promotion and primary prevention, telemedicine, capturing of patients’ bioinformatics, and full integration of clinical care with mobile application. Secondly, a proprietary telemedicine system called Tanya Pakar was developed and expedited in view of the COVID-19 pandemic. Thirdly, HUMS collaborated with Kyushu University to develop a Malaysian Portable Health Clinic which heightens rural access to tertiary level healthcare through a synergy of telemedicine, trained human capital, and portable health devices. In conclusion, OHIDAS has the potential to become a highly effective tool for health promotion and primary prevention